2021
DOI: 10.1016/j.aninu.2020.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of ramie (Boehmeria nivea) for alfalfa in improving the carcass and meat quality of Liuyang Black goats

Abstract: Ramie ( Boehmeria nivea ) is noted for the production of a large biomass that has a high protein content and is rich in antioxidants. It may thus serve as a high-quality forage material to replace alfalfa and improve the meat quality of farmed animals. In this study, we evaluated the carcass characteristics and meat quality of goats when 0, 35%, 75%, and 100% of dietary alfalfa was replaced with ramie. Crude protein content (linear, P < 0.0001) and key muscle color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The results showed that a high proportion of alfalfa in roughage could improve the antioxidant activity of mutton, but whole alfalfa could reduce daily gain and feed conversion rate. Like another study, the total use of alfalfa in the diet did not significantly improve the daily gain of livestock ( Tang et al, 2021 ). In addition, this might be related to the high content of ADF in alfalfa.…”
Section: Discussionmentioning
confidence: 70%
“…The results showed that a high proportion of alfalfa in roughage could improve the antioxidant activity of mutton, but whole alfalfa could reduce daily gain and feed conversion rate. Like another study, the total use of alfalfa in the diet did not significantly improve the daily gain of livestock ( Tang et al, 2021 ). In addition, this might be related to the high content of ADF in alfalfa.…”
Section: Discussionmentioning
confidence: 70%
“…Glu and Asp are considered the key amino acids that affect the flavor of lamb [ 65 , 66 ]. The content of DAA can directly affect the flavor of lamb [ 67 ]. Arg helps to maintain the balance between energy intake and consumption and regulates fatty acid composition, which can suppress obesity and improve meat quality [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional value of ramie is similar to that of alfalfa (Dai et al, 2019). Furthermore, ramie leaves, which are used for medicinal and edible purposes, are effective in reducing serum cholesterol, improving the meat quality of farmed animals (Avcı et al, 2006;Tang et al, 2021). Safety was always the top priority to consider when utilizing untraditional resources for animal feed purposes.…”
Section: Discussionmentioning
confidence: 99%